Neuroplasticity: A Shrouded Self-Recovery - Naveed, Muhammad Asif (Pakistan Journal of Health Sciences, 2024)
The human brain is a replica of a well-integrated universe within which light fleets in swathes and heralds the secrets of its unprecedented steadfastness and coherence. The human universe, called brain has been designed capacious enough to withhold the impacts of barter along with the adroitness of guiding the fluid dynamics of majestic human creatures. It was not until 1948 that Jerzy Konorski coined this neuro-physiological dexterity into the term ‘neuroplasticity’. The word is the true depiction of its functional mastery over making sophisticated humans adapt to any sort of internal or external change in the environment, through sharing the intense impulses of response with the neurons in closer proximity. This commitment to adaptation leads to either a renovated, recess, or re-establishment relay of neuron connections in brain, named synapses. This mechanism of self-recovery has been recently incorporated into practical therapy, owing to the flush of discoveries, enlightening both the people of science and laymen with its benefits. Neuroplasticity has been applied in the models of nervous degeneration, cognition, learning, and memory decline translating into flabbergasting outcomes among patients of Alzheimer, stroke, traumatic brain injury, epilepsy, and aging deterioration [1]. The technique has also unwound its potencies to psychologist and psychosocial activists that now recommend neuroplasticity-stimulating exercises to patients of depression and anger issues. A Question arises on how such a complete package of control is achieved by humans. Research shows and argues that it can be attained in a myriad of ways, no one roadmap has yet been formulated. Certain proteins, molecular switches, high fat diets, muscle vibrations, enforced habitual reinforcements, and conditional piquing of neurons’ originator cells onset and drive the plasticity of the neurons. A contemporary scientific investigation on the effects of virtual reality exposure to rats concluded that it fine-tuned the hippocampus region of the brain unveiled through ‘eta’ waves that were associated with storing memory [2]. Debates are underway whether neuroplasticity is the facilitator of new cranial rewiring or simply an enhancer of existing brain abilities. Future implications of neuroplasticity include its manifestation in the guise of artificial intelligence (AI). The success in proliferation of AI has been counter-argued with the extent of its ability to interpret and respond to unexpected and untaught stimuli. But the unearthing of systems such as SynapShot, a real time fluorescent apparatus developed to visualize brain’s impulse connections, heralds a before long translation of neuroplastic codes into machine language [3]. To arrive at such approaches the need of hour is to fully unlock and explore the mightiness of the plasticity horizons of the neurons, that imitate the ideology of galaxies.